Collaborative Performances of Wine Tourism Destinations in the Northern Rhone Valley - Daria Hołodnik (European Management Studies)
Purpose: The main aim of this article was to identify the wine tourism destination models set up on collaborative performances driven by Tourism Offices (Destination Marketing Organization, DMO) and wineries (private enterprises) from the appellate areas in the Northen Rhone Valley. Design/methodology/approach: The ethnographical methodology was used, including methods of participating observation (applied by a mysterious tourist method), study tours (to explore the study field), expert analysis (based on knowledge exchange with Tourism Office Managers) and official interviews (with Mangers of small and large wine producers from the areas). Findings: Two of the three surveyed wine tourism destinations from the Northern Rhône Valley (Vienne Condrieu and Rhône Crussol) are distinguished by the very active role of tourism organizations in building collaborative wine tourism offerings, in particular with small wineries. The third destination surveyed (Ardèche Hermitage) is more oriented toward collaborations with large wine producers and their independent role in leading wine tourism marketing. Research limitations/implications: Managers of tourism organizations should be oriented toward collaboration with both: large and small wine producers. Large wineries are helpful in raising the visibility and image of a wine destination. Small producers, on the other hand, offer a distinctive and individual wine tourism experience. Originality/value: The key aspect of wine tourism marketing is the building of collaborative wine tourism offerings led by DMO’s collaboration with both large and small wineries from the destination.